Health facility use by dengue patients in the Klang Valley, Malaysia: a secondary analysis of dengue surveillance data - Woon, Yuan Liang; Ng, Chiu Wan; Mudin, Rose Nani; Suli, Zailiza (Western Pacific Surveillance and Response, 2019)
Background: Dengue patients in Malaysia have the choice to seek care from either public or private sector providers. This study aims to analyse the pattern of health facility use among dengue patients to provide input for the ongoing policy discussion regarding public–private integration. The focus of this study is in the Klang Valley, which has a high dengue burden as well as a high number of private facilities.Methods: This is a cross-sectional study using an available secondary data source – the Malaysian national dengue passive surveillance system, e-Dengue registry. A total of 61 455 serologically confirmed dengue cases from the Klang Valley, registered in year 2014, were included. We retrospectively examined the relationship between demographic factors and the choice of health-care sector by logistic regression.Results: The median age of the cohort was 26 (interquartile range: 17 to 37) years. More private facilities (54.4%) were used for inpatient care; more public facilities (68.2%) were used for outpatient care. The Chinese and urban populations showed significantly higher use of the private health-care sector with an adjusted odds ratio of 4.8 [95% confidence interval (CI): 4.6–5.1] and 2.3 (95% CI: 2.2–2.4), respectively.Conclusion: Both public and private health facilities bear significant responsibilities in delivering health-care services to dengue patients. The workload of both sectors should be included in future health policy planning by public agencies.